Spiritual Education Dimensions in Bejeleng Tradition: A Sociocultural Approach to the Sasak Muslim Community in Lombok, Indonesia - Lenny Herlina (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Spiritual education in Indonesia, including in Lombok, occurs not only within formal settings such as schools but also becomes internalised within local cultural traditions. One such tradition is Bejeleng within the Sasak Muslim community in Lombok. Bejeleng is a sacred tradition of coconut oil production imbued with spiritual, social, and moral values, which have been passed down through generations. This study adopts a descriptive ethnographic method over a period of two years (2023–2024) with a participatory observation approach, in-depth interviews with 10 key informants consisting of religious leaders, organisers of the tradition’s events, and participants, as well as visual and audio documentation at Pondok Pesantren Thohir Yasin, East Lombok. The research identifies seven main dimensions of spiritual education: worship and purity within ritual processes, reinforcement of collective belief, cross-generational involvement in spiritual activities, the social and medical function of oil as a medium of learning, discipline and perseverance in ritual practice, belief in spiritual power, and the transmission of spiritual values across generations. These seven dimensions form three conceptual pillars of spiritual education: religious transcendence, collective socialisation, and the transfer of knowledge and character. The Bejeleng tradition serves as an effective social learning space for internalising spiritual values and organically building community solidarity. This finding enriches the understanding of non-formal Islamic education rooted in local culture by emphasising social interaction and collective practice as the primary media for spiritual learning. The study also suggests the development of an adaptive, inclusive Islamic education model that is rooted in local socio-cultural contexts. The limitations of this research include its focus on a local community and context-specific qualitative data; therefore, further studies with a comparative approach and quantitative methods are recommended to expand the validity of the findings and geographical coverage.